The Nutritional Education Teaching for Postnatal Mothers - Radhamohan Mudgal,; Dr. Charan Singh, (International Journal of Scientific Research in Science and Technology, 2024)
Background: Mothers in Rajasthan, have low levels of nutrition education. They do not have adequate access to the media to expand their nutrition knowledge. Malnutrition is the major cause of disease burden in developing countries and is a principal factor inhibiting further rapid declines in child mortality. Introduction: Nutrition is the most important role in the growth and development of physical, and psychological growth of young children (American Academy of Pediatrics 2016). Millions of children are eating more than what they do not need, and millions are eating too little of the requirement. Aim/Objectives: To evaluate the Effectiveness of nutrition educational teaching (NET) on knowledge regarding recommended nutrition among mothers of children under 2 years of age in the experimental group. Methodology: Quasi-experimental pre-test and post-test research design was used to collect data from mothers. A total of 300 mothers were enrolled on the study by using a purposive sampling technique. The structured knowledge questionnaire was used to assess the knowledge regarding a balanced diet before and after nutrition educational teaching. Result: The data were gathered and analyzed by using descriptive and inferential statistics. In post-test knowledge score the knowledge of mothers was Adequate 138(92%), moderate 12(8%) in the experimental group however knowledge of mothers was moderate 59(39.3%) and inadequate 91(60.7%) in control groupThere is no significance association between the level of scores and other demographic variables Marital status, religion, Type of family, type of family, type of meal intake, occupation, Family income, previous knowledge, and source of knowledge. The calculated chi-square values were less than the table value at the 0.05 level of significance. The study findings revealed that the mothers had moderately adequate knowledge regarding dietary practices in the prevention of malnutrition. Conclusion: As a result of the study, it was concluded that a mother's education helps the child's development and this is closely related. NET knowledge will help them to improve their knowledge of nutrition
Keywords: Knowledge; Nutrition Educational teaching; Mothers; Nutrition; Prevention